The Development of Digital Module for Natural Sciences to Improve Islamic Elementary School Students’ Learning Outcomes - Wina Mariana Parinduri; Titin Rahmayanti Rambe; Diah Kesumawati; Togue Nana Dipanda Franklin (Program Studi PGMI UIN Salatiga, 2022)
This study aims to develop a digital module in science learning to improve student learning outcomes. To this end, the research and development using the ADDIE model were applied. This research was conducted at Madrasah Ibtidaiyah Negeri 12 Langkat during the even semester of the 2021/2022 academic year. The study participants were fifth-grade students in Madrasah Ibtidaiyah Negeri 12 Langkat. The object of this research was the development of digital-based modules. Data were collected through observation, interviews, and documentation. The developed product was validated by three validators: a linguist, a media expert, and a material expert. Students' responses were also garnered. The developed digital module was proven to improve students’ learning outcomes 77.27% of students said they were happy with the subject matter and 86.36% of students were happy with the module components. Meanwhile, 72.73% of students were happy with the classroom learning atmosphere, and 86.36% of students were happy with the teacher's teaching method. The results of the assessment of the digital module showed that the product was deemed feasible. Students' responses to the digital module were very good. The digital science learning module developed in this study was proven to be able to improve the learning outcomes of fifth-grade students in Madrasah Ibtidaiyah Negeri 12 Langkat. This study contributes to the development of e-learning media in elementary education.